EROSI DAN SEDIMENTASI DI DAERAH ALIRAN SUNGAI (DAS) CITARUM HULU DAN UMUR OPERASIONAL PLTA SAGULING - -, Edi Tri Haryanto (Bulletin of Scientific Contribution, 2013)
Upper Citarum Catchments Area which is a function as buffer of Saguling Dam, has been pressuring to bear heavy loads. Various studies have been done, but still required analysis, discussion and identification of sources of erosion, and sedimentation that affect the operational life time of Saguling Hydroelectric Power Dam . The rate of erosion and sedimentation analysis done based on secondary data research / previous measurement. Satellite imagery "Google-earth" was interpreted, then performed field observation. Change of land use / land cover imply for increasing the value of CP. Total erosion in the upper Citarum Catchment was 15,206,301 tons / ha / yr. Deposition in the reservoir in 2002 was 4,197,152 tons, so the "Sediment delivery ratio" was 27.6%. Based on deposition data in reservoirs of the Year 1987-2007, the operational life time of hydroelectric power is expected to 56 years from 59 years of planned or "dead storage" will be exceeded in 1942..